Potential Peptide Biomarkers and Etiological Factors in the Cerebrospinal Fluid of Amyotrophic Lateral Sclerosis Patients - Wormser, Uri; Sintov, Amnon; Vinceti, Marco; Mandrioli, Jessica; Brodsky, Berta; Proscura, Elena; Finkelstein, Yoram (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by the loss of upper and lower motor neurons, which eventually may lead to death. In spite of intensive research on the molecular and cellular mechanisms involved in the etiology of ALS initiation and progression, it is, unfortunately, poorly understood and there is no efficient specific/decisive treatment for ALS patients. Critical to the mission of developing effective therapies for ALS is the discovery of biomarkers that can illuminate mechanisms of neurodegeneration and have diagnostic, prognostic, or pharmacodynamic value. Here, we merged unbiased discovery-based approaches and targeted quantitative comparative analyses to identify proteins that are altered in cerebrospinal fluid (CSF) from patients with ALS. This study aims to identify specific peptides in the cerebrospinal fluid (CSF) of ALS patients and to examine their potential relevance to the etiology of this disease. Peptides were identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Motor activity of mice was tested by the Rota-rod test and peptide-induced inflammation was assessed by induction nitric oxide synthase activity in BV2 microglia cells. Analysis of CSF samples of ALS patients (n = 15) detected two peptides, C-terminal fragments of transthyretin and osteopontin, which were absent in a control group (n = 15). In addition to being potential biomarker candidates, the relevance of these peptides to the disease etiology was tested by assessing their effects on motor activity in mice and inflammation model in cell culture. Intranasal administration of the peptides reduced motor activity in the Rota-rod test and activated lipopolysaccharide-induced inflammation in BV2 microglia cells. The mechanism of action of the neurotoxic activity may be direct cytotoxicity to neuronal cells causing necrotic/apoptotic effect and/or via LPS coactivation of microglia and elicitation of inflammatory response resulting in neuronal damage. Future studies are needed to explore the mechanism of action of these neurotoxic peptides. The results imply that two potentially neurotoxic peptides are created, released, or penetrated the central nervous system during the beginning and progression of ALS, causing neuroinflammation and neurodegeneration.